Dairy processing and quality assurance - Chandan, Ramesh C.; Kilara, Arun; Shah, Nagendra P. (John Wiley & Sons, 2016)
Describes the processing and manufacturing stages of market milk and major dairy products, from the receipt of raw materials to the packaging of the products, including the quality assurance aspects. The book begins with an overview of the dairy industry, dairy production and consumption trends. Next are discussions related to chemical, physical and functional properties of milk; microbiological considerations involved in milk processing; regulatory compliance; transportation to processing plants; and the ingredients used in manufacture of dairy products. The main section of the book is dedicated to processing and production of fluid milk products; cultured milk including yogurt; butter and spreads; cheese; evaporated and condensed milk; dry milks; whey and whey products; ice cream and frozen desserts; chilled dairy desserts; nutrition and health; sensory evaluation; new product development strategies; packaging systems; non-thermal preservation technologies; safety and quality management systems; and dairy laboratory analytical techniques. This fully revised and updated edition highlights the developments which have taken place in the dairy industry since 2008. The book notably includes: New regulatory developments; The latest market trends; New processing developments, particularly with regard to yogurt and cheese products; Functional aspects of probiotics, prebiotics and synbiotics; A new chapter on the sensory evaluation of dairy products.
Keywords: Dairy processing.; Dairy products -- Quality control.; elektronické knihy; electronic books